The ability of the philosophy of religion in Kurdish proverbs, such as the proverbs of Sheikh Mohammed Khal It is a sociolinguistic study - Karim, Asst. Prof. Dr. Aso Abdulrahman (Sulaimani Journal for Humanities, 2023)
Linguistics is a science that is closely related to all other sciences. In modern linguistics, functional linguistics, especially sociolinguistics, is directly related to society, which is the national wealth of culture and culture Folklore has its literary and literary aspects. One of the aspects of folklore is the proverbs of the ancestors, which are oral products. This research entitled (The Ability of the Philosophy of Religion in Kurdish Proverbs, the Proverbs of Sheikh Mohammed Khal as an Example) from the perspective of sociolinguistics (cozmanavani) according to the needs of the research, the meaning of the proverbs and their ability The philosophy of religion in Kurdish proverbs is analyzed with data and statistics in the proverbs of Sheikh Mohammed Khal. The study consists of two main parts. In the first part, which is the theoretical part, for the first part, religion and the philosophy of religion and its power over language are presented. In the second part, the definition of proverbs, their characteristics and effects are presented with necessary examples. The second part of the research is to practically analyze the ability of religious philosophy, Islam on the teachings of Sheikh Mohammed Khale from the perspective of sociolinguistics and semantics and statistics of this influence on The proverbs of Sheikh Mohammed Khal in the book (Proverbs of the Ancients) are presented in the result.
Keywords: Sociolinguistics; philosophy of religion; proverbs; meaning of proverbs; culture